Aid Effectiveness in Rebuilding the Afghan Health System : A Reflection - Dalil, Suraya; Newbrander, William; Loevinsohn, Benjamin; Naeem, Ahmad Jan; Griffin, James; Salama, Peter; Momand, Faiz Mohammad (Taylor and Francis, 2014)
The Paris Declaration defined five components of aid effectiveness: ownership, alignment, harmonization, managing for results and mutual accountability. Afghanistan, which has received a high level of donor aid for health since 2002, has seen significant improvements in health indicators, expanded access to health services and an increased range of services. Do the impressive health outcomes in this fragile state mean that aid has been effectively utilized? The factors that contributed to the success of the Ministry of Public Health (MOPH)-donor partnership include as follows: Ownership: a realistic role for the MOPH as the steward of the health sector that was clearly articulated to all stakeholders; Donor alignment: donor coordination and collaboration initiated by the MOPH; Joint decisions: participatory decision-making by the MOPH and donors, such as the major decision to use contracts with nongovernmental organizations for health service delivery; Managing for results: basing programs on available evidence, supplementing that evidence where possible and performance monitoring of health-sector activities using multiple data sources; Reliable aid flows: the availability of sufficient donor funding for more than 10 years for MOPH priorities, such as the Basic Package of Health Services, and other programs that boosted system development and capacity building; Human factors: these include a critical mass of individuals with the right experience and expertise being deployed at the right time and able to look beyond agency mandates and priorities to support sector reform and results. These factors, which made aid to Afghanistan effective, can be applied in other countries.